Impact of Clinical Pharmacy Expansion within a Rural Federally Qualified Health Center through Implementation of Pharmacist-Led Medicare Annual Wellness Visits - Carrington Royals; Reagan K. Barfield; Mary Francis Newman; Lori Mor; Tammy H. Cummings; P. Brandon Bookstaver (MDPI AG, 2022)
Medicare Annual Wellness Visits (AWVs) are annual appointments with the primary care team to prepare personalized prevention plans and focus on gaps in care. Although beneficial, AWVs are often difficult for providers to schedule and complete due to the increased time commitments compared to other visits. The purpose of this study was to assess the clinical, economic and patient-level value of newly implemented pharmacist-led AWVs within a rural Federally Qualified Health Center (FQHC). This retrospective, cohort study included patients who completed an AWV between 1 October 2021, and 14 February 2022. The primary objective was to compare the per clinician rate of completed AWVs between pharmacists and providers. The secondary objectives were to compare revenue generated, interventions made, and patient satisfaction between pharmacist- and provider-led AWVs. During the study period, nine providers completed 139 AWVs (15.4/provider) and two pharmacists completed 116 AWVs (58/pharmacist). Proportions of interventions ordered among those due in eligible patients were similar between pharmacists and providers (47.6% vs. 44.5%; p = 0.356). Patient satisfaction was overall positive with no difference between groups. Pharmacist-led AWVs increased completion of AWVs by 83% over a 20-week period, including significantly more initial, compared to subsequent, AWVs than providers. Sustainability of pharmacist-led AWVs at this FQHC is supported by study outcomes.